Some Notes About the Current Researches on the Physics of Relativistic Jets - Foschini, Luigi (Frontiers in Astronomy and Space Sciences, 2022)
Some highlights of the recent researches in the field of relativistic jets are reviewed and critically analyzed. Given the extent of the available literature, this essay symbolically takes the baton from the outstanding and recent review by Blandford, Meier, and Readhead (2019). Therefore, I focus mostly on the results published during the latest few years, with specific reference to jets from active galactic nuclei.